Posterior Urethral Valve Presentation, Management and Outcome (Global Journal of Medical Research, 2013)
The most common cause of lower urinary tract obstruction in male infants is posterior urethral valves with an incidence about one patient in each 5000–8000 infants [1]. A better understanding of the exact cause of the congenital obstruction of the male posterior urethra, prevention of postnatal bladder and renal injury, and the development of safe methods to treat urethral obstruction prenatally (and thereby avoiding the bladder and renal damage due to obstructive uropathy) is the goals for the care of children with posterior urethral valves [2].